KETERLIBATAN AKUNTANSI MANAJEMEN LINGKUNGAN DAN STRATEGI OPERASI TERHADAP INOVASI PROSES PRODUKSI - Retno Mustika Dewi; Annisa Fatimah; Nurafni Eltivia (Jurnal Akuntansi Indonesia, 2020)
This study examine the effect of the implementation of environmental management accounting and operation strategy on the innovation of production process. The analysis method used was multiple linear regression. The results of the study showed that environmental management accounting affected the production process innovation. The second hypothesis concluded that the operating strategy had no effect on the innovation of the production process. Simultaneous result showed that the environmental management accounting and operating strategies had a significant positive effect on the innovation of the production process